E/Z isomerization effects on aggregation-enhanced emission of tetraphenylethene derivatives assisted by host–guest recognition. Issue 61 (8th August 2017) - Li, Lijie; He, Lipeng; Liu, Xiaoning; Liu, Haomin; Hu, Linlin; Guo, Pingxia; Bu, Weifeng
Abstract : Pure E and Z stereoisomers of tetraphenylethene derivatives functionalized with dibenzylamine groups were isolated. Both supramolecular polymerization and photophysical changes were more significant in the case of the former than in the latter. Abstract : Pure stereoisomers of tetraphenylethene derivatives functionalized with dibenzylamine groups, E and Z conformers, were successfully synthesized. Their aggregation-enhanced emissions, which occurred through host–guest recognition with a dibenzo-24-crown-8 based tetraphenylethene under an acid condition, showed recognizable isomerization effects.